2020
DOI: 10.1039/d0mh01085e
|View full text |Cite
|
Sign up to set email alerts
|

A structural chemistry look at composites recycling

Abstract: Composite materials, especially carbon fiber-reinforced polymers (CFRPs), are an emerging class of structural materials now commonly used in aircraft, marine, and other applications, with emerging large-scale use in the automotive...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
62
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 43 publications
0
62
0
Order By: Relevance
“…It might be attributed to the strong mechanochemical action in the S3M process, which destroyed the ether bond and other chemical bonds of the WEP, forming numerous functional groups such as methylene, amino, and hydroxyl groups. The increase in carbonyl content was attributed to the oxidation of part of the methylene and hydroxyl groups in the WEP under strong mechanochemical action and heat (generated during equipment operation) to form carbonyl groups . EDX test showed that the oxygen content of the WEP powder increased significantly after the S3M treatment (Table S1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It might be attributed to the strong mechanochemical action in the S3M process, which destroyed the ether bond and other chemical bonds of the WEP, forming numerous functional groups such as methylene, amino, and hydroxyl groups. The increase in carbonyl content was attributed to the oxidation of part of the methylene and hydroxyl groups in the WEP under strong mechanochemical action and heat (generated during equipment operation) to form carbonyl groups . EDX test showed that the oxygen content of the WEP powder increased significantly after the S3M treatment (Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, weak bonds in the WEP would be destroyed first, such as C 6 H 5 O-CH 2 and C–N bonds, the bond strengths of which were 268 and 305 kJ/mol, respectively. , Some stronger bonds like C–C bond with a bond strength of 332 kJ/mol would be broken with further milling, destroying the crosslinking structure of the WEP. After these bonds were broken, a large number of free radicals would be generated, and those free radicals could react with water and oxygen in the air or other radicals to produce some new alkanes, alcohols, and other substances . As a result, the number of groups such as hydroxyl, amino, methyl, and methylene increased significantly.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The crucial drawback of composites is that they are challenging to recycle, especially carbon fiber-reinforced composites due to their hardness and chemical stability [ 6 ]. However, the significant commercial value of carbon fiber-reinforced composites recycling lies in recovering long high modulus fibers with a high intrinsic value for their reuse in high-grade applications.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is difficult to replace the existing thermosetting plastics due to poor properties and high cost. Chemical recovery is regarded as a more promising method because it can produce useful chemicals and potentially achieve upcycling [6,17–19] . However, the highly crosslinked three‐dimensional network makes it quite difficult for the epoxy thermosets to undergo degradation [20–27] .…”
Section: Introductionmentioning
confidence: 99%